Thraatchathi chooranam, protects cardiomyocytes against oxidative stress - Ganapathy, Ramakrishnan; Mani, Sugumar; Raghavendran, Hanumanth Rao Balaji; Kamarul, Tunku; Ray, Bipul; Bhat, Abid; Chidambaram, Saravana Babu (Frontiers in Bioscience, 2018)
Thraatchathi Chooranam (TC), is a polyphenol-rich Indian traditional medicine. Present study was undertaken to investigate the effects of TC against H2O2 induced oxidative stress and apoptotic damage in H9C2 cardiomyocytes. Cell viability assay indicated relative safety (IC50= 488.10±12.04 mg/ml) of TC. Pretreatment of cells with TC upregulated antiapoptotic Bcl2, and anti-oxidants TRX1 and TRXR and downregulated Bax and HIF-α and inflammatory genes iNOS and TNF-α. Together, these findings show that TC has both anti-oxidant and anti-apoptotic properties. Further studies may be considered to identify the bioactive principle(s) and precise mechanisms of action of TC.